Compartmental absorption modeling and site of absorption studies to determine feasibility of an extended‐release formulation of an HIV‐1 attachment inhibitor phosphate ester prodrug. Issue 6 (5th April 2013) - Brown, Jonathan; Chien, Caly; Timmins, Peter; Dennis, Andrew; Doll, Walter; Sandefer, Erik; Page, Richard; Nettles, Richard E.; Zhu, Li; Grasela, Dennis
Abstract BMS‐663068 is a phosphonooxymethyl ester prodrug under development for the treatment of HIV/AIDS. The prodrug is designed to overcome the solubility‐limited bioavailability of the active moiety, BMS‐626529. BMS‐663068 is not absorbed from the gastrointestinal (GI) tract and requires enzymatic conversion by alkaline phosphatase to BMS‐626529 immediately before absorption. In the light of the known short in vivo half‐life of BMS‐626529, compartmental absorption modeling was used to predict the potential feasibility of extended‐release (ER) delivery to achieve target Cmax:Cmin ratios. To further refine the model with respect to colonic absorption, the regional absorption of BMS‐626529 following delivery of BMS‐663068 to upper and lower GI sites was characterized through a site of absorption study in human subjects. A refined model was subsequently applied to guide the development of ER tablet formulations. Comparisons of results from the refined model to the in vivo human pharmacokinetic data for three selected ER formulations demonstrate the utility of the model in predicting feasibility of ER delivery and in directing formulation development. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:1742–1751, 2013